2008
DOI: 10.1073/pnas.0805965105
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated evolution of resistance in multidrug environments

Abstract: The emergence of resistance during multidrug chemotherapy impedes the treatment of many human diseases, including malaria, TB, HIV, and cancer. Although certain combination therapies have long been known to be more effective in curing patients than single drugs, the impact of such treatments on the evolution of drug resistance is unclear. In particular, very little is known about how the evolution of resistance is affected by the nature of the interactions-synergy or antagonism-between drugs. Here we directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
329
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(363 citation statements)
references
References 29 publications
14
329
1
1
Order By: Relevance
“…This importance and clinical relevance is because highly synergistic triple-drug combinations are of utmost importance due to the high efficacy of the treatment compared with pairwise interactions [1,[36][37][38][39][40]. On the other hand, identifying suppressive interactions may be especially valuable because it has been shown that, counterintuitively, these interactions may slow and thus suppress the evolution of antibiotic resistance [8,15,17,[41][42][43]. That is, there may be a trade-off between killing efficiency and the evolution of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This importance and clinical relevance is because highly synergistic triple-drug combinations are of utmost importance due to the high efficacy of the treatment compared with pairwise interactions [1,[36][37][38][39][40]. On the other hand, identifying suppressive interactions may be especially valuable because it has been shown that, counterintuitively, these interactions may slow and thus suppress the evolution of antibiotic resistance [8,15,17,[41][42][43]. That is, there may be a trade-off between killing efficiency and the evolution of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, Torella et al (2010) developed a mathematical model for the evolution of multidrug resistance under synergistic and antagonistic drug interactions (implementing no form of recombination). The model shows that resistance evolves less easily under antagonistic interactions but again only if competition among cells is high (for experiments, see Hegreness et al 2008). Our results suggest that even without competition, antagonistic drug interactions (with a relatively fit wild type but unfit single mutants) can strongly hamper the evolution of resistance for infections with pathogens that readily recombine in vivo, such as HIV.…”
mentioning
confidence: 86%
“…Moreover, although our model optimized for overall efficacy by targeting all subpopulations, an optimal drug combination would require further understanding of how differential selective pressures imposed by drugs affect the potential for secondary resistance. This issue has been studied particularly in antibiotic resistance, in which strong selection by synergistic drug combinations actually may increase the risk of resistance (33,34). Ultimately, just as multiobjective optimization approaches may be applied to derive small molecule structures with the desired polypharmacological profiles (35), a multiobjective optimization with considerations of these additional properties provides a potentially promising approach to optimizing drug combination in the context of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%